The expression of the F-box protein Skp2 is negatively associated with p27 expression in human pituitary tumors. - Musat, M; Korbonits, M; Pyle, M; Gueorguiev, M; Kola, B; Morris, D; Powell, M; Dumitrache, C; Poiana, C; Grossman, AB (2002)
The CDK inhibitor p27 plays a pivotal role in controlling cell proliferation during development, and has been implicated in tumorigenesis. Previous studies have demonstrated changes in p27 protein expression, but not in mRNA levels, in human pituitary tumors. It seems probable that the fall in p27 is due to increased degradation through the ubiquitin-proteasome pathway. Skp2 (S-phase kinase-interacting protein) is a specific F-box protein that allows the recognition and binding of phosphorylated p27 to the ubiquitin complex. The aim of our study was thus to investigate the possible role of Skp2 in pituitary tumorigenesis. A total of 59 human pituitary samples, 7 normal and 52 adenomas, were assessed for transcriptional expression of Skp2; 51 pituitary samples were assessed for protein expression. Real-time RT-PCR was performed on cDNA of reverse-transcribed mRNA for relative quantification of the Skp2 transcript. Immunostaining was performed using mouse monoclonal anti-Skp2 antibody. Skp2 mRNA and protein was detectable in every sample studied. Our results showed no significant difference between the pituitary tumors and normal pituitary tissue in Skp2 mRNA or nuclear protein expression. Individual tumor types had similar mRNA expression and variable protein expression. However, samples with high p27 protein expression showed significantly less Skp2 expression than samples with low p27 staining. Our data suggest that increased p27 degradation through the ubiquitin-proteasome pathway could be regulated in pituitary tumors by changes in Skp2 expression, although other factors probably also play a role.